2006
DOI: 10.1007/s11103-006-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Cystathionine-γ-Synthase and de novo Synthesis of Methionine in Ethylene Production during tomato Fruit Ripening

Abstract: The essential amino acid methionine is a substrate for the synthesis of S-adenosyl-methionine (SAM), that donates its methyl group to numerous methylation reactions, and from which polyamines and ethylene are generated. To study the regulatory role of methionine synthesis in tomato fruit ripening, which requires a sharp increase in ethylene production, we cloned a cDNA encoding cystathionine gamma-synthase (CGS) from tomato and analysed its mRNA and protein levels during tomato fruit ripening. CGS mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…22 -limiting conditions, efficient recycling of Met (in the Yang cycle) becomes vital in addition to a de novo synthesis (Kushad et al, 1985(Kushad et al, , 1988Sauter et al, 2005;Katz et al, 2006;Bürstenbinder et al, 2007). Compared with N. attenuata wild-type seedlings, control 35S-etr1 seedlings accumulated higher basal transcript levels of genes involved in Met biosynthesis (Na-CGS542 and Na-MS90), SAM synthesis (Na-SAMS113), and Met recycling in the Yang cycle (Na-MTK3797).…”
Section: Discussionmentioning
confidence: 99%
“…22 -limiting conditions, efficient recycling of Met (in the Yang cycle) becomes vital in addition to a de novo synthesis (Kushad et al, 1985(Kushad et al, , 1988Sauter et al, 2005;Katz et al, 2006;Bürstenbinder et al, 2007). Compared with N. attenuata wild-type seedlings, control 35S-etr1 seedlings accumulated higher basal transcript levels of genes involved in Met biosynthesis (Na-CGS542 and Na-MS90), SAM synthesis (Na-SAMS113), and Met recycling in the Yang cycle (Na-MTK3797).…”
Section: Discussionmentioning
confidence: 99%
“…Although we were not able to detect ET levels in the developing seeds, we suspect that its levels increased, since we found that several key genes involved in its synthesis and downstream targets were up-regulated. We previously showed a strong correlation between higher Met content and higher ET levels in tomato (Solanum lycopersicum; Katz et al, 2006), suggesting that this also might occur in SSE seeds. The higher germination rates of SSE seeds in the presence of ACC, the substrate for ET synthesis, also supports this assumption.…”
Section: Seed-specific Expression Of Atd-cgs Stimulates Transcriptomimentioning
confidence: 92%
“…However, additional evidence suggests that in addition to recycling the Met moieties via the Yang cycle, the de novo synthesis of Met is required when high rates of ethylene production are induced. 79 Moreover, S availability and ethylene have been shown to regulate GSH synthesis and stress tolerance to ozone 80 and Cd 81,82 stress. Glutathione acts as a storage and transport form for Cys; otherwise the excess Cys present in the cell becomes toxic.…”
Section: Ethylene Cross-talk Associated With Sulfurmentioning
confidence: 99%